Tinjauan Yuridis Tindak Pidana Kekerasan terhadap Aparat yang sedang Melakukan Tugas yang Sah : Studi Kasus Penyerangan terhadap Anggota Polrestabes Medan - Yohanes Mosargadhajo; Misbahul Huda; Iwan Usmansyah (HUMANIORUM, 2023)
Several legal events that have taken place in recent years show increasingly flexible motives due to the impact of the times. One of them is the phenomenon of acts of violence that even occur in the community environment by involving police officers as law enforcers, both between officers and the community and fellow officers. This research aims to review from a juridical perspective the criminal act of violence against officials who are carrying out legal duties as a case study of the assault of a bookie and his group on members of the Medan Police who were carrying out their duties of raiding gambling places which are prohibited by law. The type of research used in this research is normative legal research with the method of literature study originating from primary legal material, namely the Criminal Code. The results of this study concluded that based on the Criminal Code, crimes committed by perpetrators in relation to assaults on members of the police can fulfill 3 multi-layered articles, namely Article 351 paragraph (2) of the Criminal Code concerning persecution causing serious injury with a maximum threat of 5 years imprisonment, Article 170 paragraph (2) 2nd of the Criminal Code regarding beatings which resulted in serious injury with a maximum threat of 9 years in prison, and Article 212 of the Criminal Code concerning acts of violence against officers with a maximum threat of 1 year and 4 months in prison. As for the provisions of multiple articles, it is regulated in Article 65 of the Criminal Code, namely that the threat is only one sentence with the basic criminal provisions of the same type with the most severe punishment but may add one third to a sentence.